2004
DOI: 10.1038/sj.jhh.1001771
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic differences in prehypertension in American adults: Population and relative attributable risks of abdominal obesity

Abstract: To estimate the risk and population attributable risk of prehypertension that is due to abdominal obesity in White, Black and Hispanic American adults. To determine how much of the relative difference in the risk of prehypertension between high-risk Blacks and Hispanics and the low-risk group Whites that is attributable to their differences in abdominal obesity. Data (n ¼ 4016) from the 1999 to 2000 US National Health and Nutrition Examination Surveys were used in this study. Abdominal obesity was defined as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 22 publications
3
42
0
Order By: Relevance
“…But it is striking that even though the black South Africans have higher BPs, vascular resistance, fibrinogen and leptin levels than Caucasian women, the relationships of these risk markers with obesity are significantly weaker than those of Caucasians. Okosun et al 22 found opposite results, namely that abdominal obesity of African-American women was more strongly associated with increased odds of prehypertension than for Caucasian women. However, it remains uncertain as to what extent South African and African-American populations could be compared.…”
Section: Discussionmentioning
confidence: 75%
“…But it is striking that even though the black South Africans have higher BPs, vascular resistance, fibrinogen and leptin levels than Caucasian women, the relationships of these risk markers with obesity are significantly weaker than those of Caucasians. Okosun et al 22 found opposite results, namely that abdominal obesity of African-American women was more strongly associated with increased odds of prehypertension than for Caucasian women. However, it remains uncertain as to what extent South African and African-American populations could be compared.…”
Section: Discussionmentioning
confidence: 75%
“…Due to the relatively older age and small study sample, further study is needed to clarify when prehypertension is of the same prognostic value in older people as in the adult and middle-aged population. In addition, it has been reported that DM and impaired glucose tolerance were significantly increased in prehypertensive subjects, and their influences extended into hypertensive subjects 27,28) . There are several limitations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that diet, obesity, social support, and stress may contribute, but these factors do not seem to fully explain higher Black BP. [2][3][4] Vitamin D is critical to bone health, but ubiquitous vitamin D receptors and effects on myriads of genes suggest broader clinical effects. 5 Genetic knockout models suggest vascular effects of vitamin D, including vascular endothelium, the renin-angiotensin axis, 6 and vascular smooth muscle including cell proliferation, 7 inflammation, 6 thrombosis, 8 cardiac hypertrophy, 9 and hyperparathyroid hormone secretion.…”
Section: Introductionmentioning
confidence: 99%